PENGEMBANGAN KEGIATAN BERMAIN BERBASIS PROYEK BAGI GURU PAUD DI KECAMATAN JATIBARANG KABUPATEN INDRAMAYU - Niken Pratiwi; Yuliani Nurani; Eriva Syamsiatin; Azizah Muis; Winda Gunarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Children should undertake play activities in an enjoyable and engaging environment. Early Childhood Education units in all forms of services must provide support in all elements, both physical and non-physical, so that children can develop in accordance with their developmental stages and features. This community service activity is carried out in the designated area to improve teacher competences and the quality of early childhood education services in the area covered by the S1 PGPAUD Study Program, namely in Jati Barang District, Indramayu Regency, and West Java. Early childhood education instructors in Jati Barang District, Indramayu Regency, West Java will be trained and provided with the abilities to produce engaging and fun activities as well as manage classrooms that are appropriate for children's developmental levels. This activity technique is implemented by offering support at the following stages: 1) Lecture Method; 2) Demonstration Method; and 3) Question and Answer Method. The findings of this exercise assist early childhood education teachers in generating themes and project-based play activities, notably the subject